Electrospun Single Crystalline Fork-Like K2V8O21 as High-Performance Cathode Materials for Lithium-Ion Batteries - Hao, Pengfei; Zhu, Ting; Su, Qiong; Lin, Jiande; Cui, Rong; Cao, Xinxin; Wang, Yaping; Pan, Anqiang (Frontiers in Chemistry, 2018)
Single crystalline fork-like potassium vanadate (K2V8O21) has been successfully prepared through electrospinning combined with a subsequent annealing process. The as-obtained K2V8O21 forks show a unique layer-by-layer stacked structure with conductive carbon. When used as cathode materials for lithium-ion batteries, the as-prepared fork-like materials exhibit high specific discharge capacity and excellent cyclic stability. High specific discharge capacity of 200.2 mA h g-1 and 131.5 mA h g-1 can be delivered at the current densities of 50 mA g-1 and 500 mA g-1, respectively. Furthermore, the K2V8O21 electrodes exhibit excellent long-term cycling stability that maintain a capacity of 108.3 mA h g-1 after 300 cycles at 500 mA g-1 with a fading rate of only 0.054% per cycle, revealing their potential applications in next generation high-performance lithium-ion batteries.